2022
DOI: 10.1080/21655979.2022.2050880
|View full text |Cite
|
Sign up to set email alerts
|

The effect and mechanism of miR-30e-5p targeting SNAI1 to regulate epithelial-mesenchymal transition on pancreatic cancer

Abstract: Accumulating evidence indicates that abnormally expressed microRNAs (miRNAs, miRs) contribute to cancer progression. Nonetheless, the role of miR-30e-5p in pancreatic cancer (PCa) remains unclear. In this study, using quantitative real-time polymerase chain reaction analysis, we found that miR-30e-5p expression was downregulated in human PCa tissues compared with that in normal para-cancerous tissues. After transfecting with miR-30e-5p inhibitors, miR-30e-5p mimics, or empty vectors in the BxPC-3 and PANC-1 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…[32] Besides, SNAI1 have a positive effect on the development and invasion of various tumors through inducing EMT. [33][34][35] In addition, IRX1, a member of the iroquois homeobox transcription factor family, has been identified as a tumor suppressor in several cancers, including lung adenocarcinoma, gastric cancer and invasive ductal carcinoma. [36][37][38][39] In our study, we found that high expressions of CDKN2A, SCD and SNAI1 were closely related to the poor prognosis, which was consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…[32] Besides, SNAI1 have a positive effect on the development and invasion of various tumors through inducing EMT. [33][34][35] In addition, IRX1, a member of the iroquois homeobox transcription factor family, has been identified as a tumor suppressor in several cancers, including lung adenocarcinoma, gastric cancer and invasive ductal carcinoma. [36][37][38][39] In our study, we found that high expressions of CDKN2A, SCD and SNAI1 were closely related to the poor prognosis, which was consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…miR-22 triggers EMT by inhibiting the translation of SFRP2 and PCDH15, which repress the Wnt/b-catenin pathway, essential for cell growth, invasion, and stemness [52]. miR-30e-5p inhibits cell proliferation, migration, and invasion via the targeting of snail family transcriptional repressor 1 (SNAI1), whereby the up-regulation of which is the main characteristic of EMT [53]. Additionally, it was found that the expression levels of let-7d-5p and miR-20a-5p were increased [54,55], while the expression level of let-7i-5p was decreased [56] in placental tissues or blood plasma samples collected from patients with PE.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-30e-5p had a tumor suppressor function in regulation of PC cell proliferation, EMT, and migration through SNAI1 suppression. There was also miR-30e-5p down regulation in PC tissues in comparison with normal samples [ 33 ]. MiR-199 inhibited self-renewal of gemcitabine (GEM)-treated PC cells.…”
Section: Emt Related Transcription Factorsmentioning
confidence: 99%